(untitled) (GEON Journal (Management, Organizations and Business), 2021)
The valuation of qualitative variables in teaching-learning strategies is a key factor in the development of educational strategies that strengthen learning, supported by ICT. This strengthening includes the application of innovative methodologies and didactic activities to achieve a better transmission and reception of knowledge. The objective of this research is to evaluate a technological acceptance model (TAM) based on a questionnaire addressed to teachers and students of a public institution of higher education in Medellin, Colombia, to determine the level of incidence of the variables: attitude, perceived utility, ease of use, intention and confidence, in comparison to didactic methodologies. We present a descriptive research supported by validation techniques and methods such as the Bartlett test, KMO, Cronbach’s Alpha and the convergent and discriminant validation for the constructs of the model. As a result, the degree of favorability in the perceived relevance for both traditional and innovative trends is presented, evidencing a positive association between the construct variables studied without detriment or harm in the existence of putting into action an innovative tool within the classroom.